Empirical Study Of The Effect Of The Audit Committee Characteristics On Fraudulent Financial Reporting - Jadongan Sijabat; Renata A Tamba (International Journal Reglement & Society (IJRS), 2021)
The purpose of this study was to examine the characteristics of the audit committee on fraudulent financial reporting. The characteristic variables of the audit committee studied were: the number of independent audit committees, the financial expertise of the audit committee, the frequency of audit committee meetings, and the tenure of the audit committee. The number of independent audit committees is proxied by the percentage of independent audit committees to the number of audit committee members. The financial expertise of the audit committee is proxied by the percentage of the number of audit committee experts in finance and accounting to the number of audit committee members. The frequency of audit committee meetings is measured by counting the number of meetings held in one period (one year). The tenure of the audit committee is proxied by the percentage of the audit committee serving for two consecutive terms. Fraudulent financial reporting is proxied by a calculation called the F-Score (Fraud Score). The population of this study are banking sector service companies listed on the Indonesia Stock Exchange in 2016-2019. The sample of this study was 28 companies with 4 years of observation so that the data was 112. The data analysis method used was logistic regression with SPSS version 22. The results of this study indicate that the financial expertise of the audit committee, the frequency of audit committee meetings, and the tenure of the audit committee have a negative effect on fraudulent financial reporting, while the number of independent audit committees has no effect on reducing fraudulent financial reporting.